Determine a lei da função f(x)= ax + b, sabendo que f(3)=5 e f(-1)=-7. *
1 ponto
a. f(x)= 3x - 4
b. f(x)= -3x - 4
c. f(x) = 3x + 4
d. f(x)= - x + 4
Soluções para a tarefa
Respondido por
1
Resposta:
f(x)= ax + b
f(3)=5 ==> 5=3a+b (i)
f(-1)=-7 ==>-7=-a+b (ii)
(i)-(ii)
12=4a ==>a=3
Usando (i) 5=3*3+b ==>b= -4
f(x)=3x-4
Letra A
Perguntas interessantes
Química,
7 meses atrás
Contabilidade,
7 meses atrás
História,
7 meses atrás
Matemática,
8 meses atrás
Português,
8 meses atrás
Filosofia,
1 ano atrás
Pedagogia,
1 ano atrás
Administração,
1 ano atrás